A critical review: Effects of exercise and psychosocial interventions on the body image of breast cancer survivors - Nga Ching Chan; Ka Ming Chow (Wiley, 2023)
Abstract Aim The aim of the study was to identify, summarize and critically appraise studies that have investigated the effects of exercise and psychosocial interventions on body image of breast cancer survivors. Design A critical review. Methods A comprehensive search was conducted to identify relevant articles published in MEDLINE, PsycINFO, CINAHL and British Nursing Index between 2011 and 2021. Included studies' methodological quality was assessed using the critical appraisal checklists of the Center for Evidence‐Based Management. Results A total of eight studies were included. Breast cancer survivors who received exercise or psychosocial interventions had an improved body image compared with baseline, which enhanced their quality of life. Compared with psychosocial interventions, exercise demonstrated more positive effects as they enhanced both mental and physical well‐being. Breast cancer survivors expressed that they preferred to have a knowledgeable mentor to guide and empower them throughout the exercise intervention. Psychosocial interventions showed varying effectiveness, with self‐compassion‐focused writing activity being most effective.